Fisherman Livelihood Effects on Marine Conservation Area towards Sustainable Development - Tiara Sartika Worowirasmi; Artiningsih Artiningsih (The Indonesian Journal of Planning and Development, 2018)
Excessive utilization of coastal resources is threatening the livelihood of coastal dependent people. The current challenge is how to maintain and use coastal resources sustainably without reducing their potential benefits in the future. In response to coastal sustainability issues, many countries have implemented a policy to support marine protected areas. Until 2008, approximately 3.2 million hectares of marine protected areas conserved in Indonesia. One of them located in Ujungnegoro-Roban, Batang Regency of Central Java Province, Indonesia. This study aims to analyze fisherman livelihoods in Ujungnegoro-Roban, which may affect the fishermen’s conservation choices. This study employs questionnaire survey as the main data collection source, which was distributed to 60 fishermen randomly. The findings indicated some fisherman livelihood factors which have significant support for conservation activities, i.e. age, experience, income level and fisherman organization membership.